Clinical Grading of Corneal Ulcer and Its Management in Dr. M. Djamil General Hospital, Padang, Indonesia - Amanda Priska Diananti; Havriza Vitresia; Getry Sukmawati (HM Publisher, 2023)
Background: Infectious corneal ulcer (CU) occurs due to an agent, which may be a bacterial, fungal, or viral microorganism. A detailed examination of the ulcer was needed to determine the severity grading of the ulcer. Based on the size, depth of ulcer, density of infiltrate, and scleral involvement, it's divided into mild, moderate, and severe grades and may be used to objectively monitor the progress of the ulcer and as a parameter for management. Medical management includes topical, systemic antibiotic, and periocular injection, while amniotic membrane transplantation (AMT), conjunctiva flap, fascia lata, and evisceration as surgical. This study aimed to assess the clinical grading associated with the management of CU in Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: Observational analytics based on the medical record of corneal ulcer patients in Dr. M. Djamil General Hospital, Padang, Indonesia, in 2016-2017. A total of 191 research subjects participated in this study. Data analysis was carried out using SPSS univariately. Results: The fungal, bacterial, and viral CU was diagnosed clinically. The severity grading that we found is moderate (60,73%), mild (25,14%), and severe (14,13%). All of the cases used medical treatment. Surgical was performed in moderate (36,59%) and all severe cases. AMT was performed in severe cases with perforation ≤ 4 mm and perforation > 4 mm conjunctival flap (3.7%), fascia lata (3,7%), and evisceration (61,53%), preferably. Conclusion: The clinical grading of corneal ulcers in our hospital is moderate, and it may be associated with our hospital as a referral hospital. Surgery was performed in all severe and moderate cases that don't respond well to medicine.